Composite Cryogel with Polyelectrolyte Complexes for Growth Factor Delivery - Sultankulov, B.; Berillo, Dmitriy; Kauanova, Sholpan; Mikhalovsky, Sergey; Mikhalovska, Lyuba I.; Saparov, Arman (MDPI, 2019)
Macroporous scaffolds composed of chitosan (CHI), hydroxyapatite (HA), heparin (Hep), and polyvinyl alcohol (PVA) were prepared with a glutaraldehyde (GA) cross-linker by cryogelation. Addition of PVA to the reaction mixture slowed down the formation of a polyelectrolyte complex (PEC) between CHI and Hep, which allowed more thorough mixing, and resulted in the development of the homogeneous matrix structure. Freezing of the CHI-HA-GA and PVA-Hep-GA mixture led to the formation of a non-stoichiometric PEC between oppositely charged groups of CHI and Hep, which caused further efficient immobilization of bone morphogenic protein 2 (BMP-2) possible due to electrostatic interactions. It was shown that the obtained cryogel matrix released BMP-2 and supported the differentiation of rat bone marrow mesenchymal stem cells (rat BMSCs) into the osteogenic lineage. Rat BMSCs attached to cryogel loaded with BMP-2 and expressed osteocalcin in vitro. Obtained composite cryogel with PEC may have high potential for bone regeneration and tissue engineering applications.